2017
DOI: 10.1073/pnas.1620755114
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic, proteomic, and metabolomic landscape of positional memory in the caudal fin of zebrafish

Abstract: Regeneration requires cells to regulate proliferation and patterning according to their spatial position. Positional memory is a property that enables regenerating cells to recall spatial information from the uninjured tissue. Positional memory is hypothesized to rely on gradients of molecules, few of which have been identified. Here, we quantified the global abundance of transcripts, proteins, and metabolites along the proximodistal axis of caudal fins of uninjured and regenerating adult zebrafish. Using this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 92 publications
6
84
0
Order By: Relevance
“…Perathoner et al (2014) have shown that a gain-of-function mutation in the voltage-gated potassium channel displays a long fin phenotype in adult zebrafish. Consistent with these studies, the results of the transcriptome, proteome, and metabolome analyses in regenerating fins have suggested that there is a gradient of expression of ion channels within the zebrafish fin (Rabinowitz et al, 2017). Consistent with these studies, the results of the transcriptome, proteome, and metabolome analyses in regenerating fins have suggested that there is a gradient of expression of ion channels within the zebrafish fin (Rabinowitz et al, 2017).…”
Section: Entity Of Positional Informationsupporting
confidence: 57%
“…Perathoner et al (2014) have shown that a gain-of-function mutation in the voltage-gated potassium channel displays a long fin phenotype in adult zebrafish. Consistent with these studies, the results of the transcriptome, proteome, and metabolome analyses in regenerating fins have suggested that there is a gradient of expression of ion channels within the zebrafish fin (Rabinowitz et al, 2017). Consistent with these studies, the results of the transcriptome, proteome, and metabolome analyses in regenerating fins have suggested that there is a gradient of expression of ion channels within the zebrafish fin (Rabinowitz et al, 2017).…”
Section: Entity Of Positional Informationsupporting
confidence: 57%
“…For instance, new transgenic mice, axolotls, and zebrafish have been employed to determine the sources of new cells in regenerating tissues (122). In addition, genome-wide profiling, which can be combined with new genome-editing technologies, has uncovered novel factors and concepts during tissue regeneration (13; 29; 79; 94). In this review, we focus on some of the central questions in tissue regeneration research, what has been learned recently to address these questions, and how genetic strategies have enabled these studies.…”
Section: Introductionmentioning
confidence: 99%
“…In future studies, it should be interesting to examine whether the observed thermally induced plasticity of the caudal fin is mediated by alterations of the expression of genes like fgfs, shh, bmp2b , and cx43 , which are involved in the growth and differentiation of the caudal‐fin rays (Govindan & Iovine, ; Lee, Grill, Sanchez, Murphy‐Ryan, & Poss, ; Quint et al, ; Sims, Eble, & Iovine, ; Wills, Kidd, Lepilina, & Poss, ). Such alterations might occur at the level of individual genes, or be part of a thermally induced modification of the “positional identity” gradient, a prespecification gradient that controls the position‐dependent growth and differentiation of fin rays (Mari‐Beffa & Murciano, ; Rabinowitz et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This stability could be explained by a fusion of the adjacent to the bifurcation segments, which is happening in association with the fusion of the proximal segments (Figure ). The positioning of these two fusions might be determined by the “positional identity” gradient, a prespecification gradient that controls the position‐dependent growth and differentiation of fin rays (Mari‐Beffa & Murciano, ; Rabinowitz et al, ). Anatomically, the fusion of the proximal segments of caudal lepidotrichia with fish growth might serve the insertion of growing caudal‐fin musculature, and specifically of m. interradialis which controls the individual movement of each fin ray (Flammang, ; Lauder, ).…”
Section: Discussionmentioning
confidence: 99%